1969
DOI: 10.1037/h0027035
|View full text |Cite
|
Sign up to set email alerts
|

Body movement and speech rhythm in social conversation.

Abstract: The relationship between body movement and speech rhythm was newly formulated following Boomer's work on hesitations in speech: movements were predicted to occur early in phonemic clauses and at points following nonfluencies within clauses. A preliminary study of old data for which the movements were located by watching motion pictures bore out the prediction, and led to a more intensive study using more representative speech samples, and recording techniques designed to eliminate possible artifacts. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 19 publications
3
42
0
2
Order By: Relevance
“…Of course, arguments of this sort are notoriously difficult either to support or to falsify empirically, and we are inclined to agree with Nottebaum's assessment of Hewes's proposal as "a novel idea unsupported by any compelling evidence" (Nottebaum, 1973, p. 15). In a similar vein, Dittmann and Llewelyn (1969) have suggested that gestures are more-or-less random movements whose function is to dissipate tension during lexical search. The results of these studies (especially Experiment 2) reduce the plausibility of this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, arguments of this sort are notoriously difficult either to support or to falsify empirically, and we are inclined to agree with Nottebaum's assessment of Hewes's proposal as "a novel idea unsupported by any compelling evidence" (Nottebaum, 1973, p. 15). In a similar vein, Dittmann and Llewelyn (1969) have suggested that gestures are more-or-less random movements whose function is to dissipate tension during lexical search. The results of these studies (especially Experiment 2) reduce the plausibility of this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Noting that people often gesture when they are having difficulty retrieving an elusive word from memory, Dittmann and Llewelyn (1969) have suggested that at least some gestures may be more-or-less random movements whose function is to dissipate tension during lexical search. The idea is that failures of word retrieval are frustrating, and that unless dealt with, this frustration-generated tension could interfere GSP4.2 July 30, 2001 Krauss, Chen & Got †esman -7 -with the speaker's ability to produce coherent speech.…”
Section: Tension Reductionmentioning
confidence: 99%
“…[Dittman & Uewellyn, 1969] observed that hand movements were particularly concentrated around the fllSt word of utterances. [Kendon, 1972] concludes from a speech sample analysis that when a bodily movement is precisely related to a word in a sentence, the movement in question begins before the corresponding word.…”
Section: Introductionmentioning
confidence: 96%